Demographic and clinical factors associated with change of drug regimen due to adverse drug reactions among new tuberculosis patients in the upper north and upper northeast of Thailand: A secondary data analysis from a routine regional TB reporting system - Surachet Arunothong (Faculty of Medicine, Chiang Mai University, 2019)
Chiang Mai Medical Journal (Formerly Chiang Mai Medical Bulletin) is an official journal of the Faculty of Medicine, Chiang Mai University. It accepts original papers on clinical and experimental research that are pertinent in the biomedical sciences. The Journal is published 4 issues/year (i.e., Mar, Jun, Sep, and Dec).